Satisfaction among the Insured and the Uninsured Patients visiting for OPD services in various health facilities of Kaski - Yadav, Dipendra Kumar; Kshetri, Binod Poudel; Sharma, Prabin (Nepalese Journal of Insurance and Social Security, 2020)
Health insurance is the process of financial protection against health-related poverty and catastrophic health care cost. Satisfaction of the patients is the perception towards services they get from the health institution. This study aims to assess the satisfaction level and factors associated with it among the insured and the uninsured patients visiting the OPD services in the health facilities of Kaski.Cross-sectional analytical study was conducted using purposive sampling technique. Data was collected through Face-to-face interview among 258 participants (107 Insured and 151 Uninsured) while EPI DATA and SPSS were used for the data entry and analysis respectively. Ethical approval was obtained from the institutional review committee of Pokhara University and respective health facilities and consent from each participant was taken.Insured and uninsured participants were 41.5% and 58.5% respectively. 52.3% of insured and 49% of uninsured patients were female. Among the 107 insured participants, 74.8% participants visited for the first time and 18.7% for follow up. Educational status and SHI premium affordability were associated with satisfaction of the insured. Waiting time was associated with satisfaction among the uninsured participants. Waiting time, time provided doctors related availability of medicines related to lower level of satisfaction in both participants. Majority of the insured (83.2%) and uninsured (84.8%) participants were satisfied.The study shows overall satisfaction to be good in both insured and uninsured participants; however, it is suggested to improve the health service-related factors like waiting time; time provided by the doctors and the awareness on policy among the patients for further improvement of the program in Nepalese context.